Juridical Analysis of the Acquittal in a Murder Crime - Chairul Nopriansyah (NAROTAMA UNIVERSITY, Indonesia, 2020)
The judge plays an important role in the judiciary because the judge has the authority to examine, hear and decide on a case so that he is obliged to look for values ??of justice in the application of progressive and responsive laws, so the judge in issuing decisions must pay attention to various considerations. Article 183 of the Criminal Procedure Code contains several elements of judges' considerations when making decisions. In the case of an acquittal, the judge needs carefulness and carefulness to consider so that a matter must be truly convincing. This research is a doctrinal research method that is taking the opinions of experts regarding free decisions and through legal products in the form of legislation and judges' decisions. The conclusion of this paper is First, the basic consideration of the judge in passing a free verdict (vrijspraak) is not fulfilling the minimum limit of evidence by the public prosecutor so that the judge will release the defendant because the evidence that can blame the defendant is insufficient and based on the elaboration of the writer above, the Supreme Court allows legal efforts to overturn an acquittal (vrijspraak) namely an appeal on an acquittal, but not all verdicts requested for appeal are always accepted by the Supreme Court.